Impact of Demand-Side Behavior on Line Switching and Reactive Power Management Considering Reconfiguration and Capacitor Costs - Mahdavi, Meisam; Siano, Pierluigi (Canadian journal of electrical and computer engineering, 2025)
Altering the flow of power along branch reconfiguration of radial distribution feeders and mitigating the reactive power component through optimal shunt capacitor placement are proven methods for reducing energy losses in distribution systems. However, it is crucial to recognize that variations in load demand can significantly impact the magnitude of these energy losses and reactive power installation costs, potentially influencing the optimal placement of capacitors and the strategy for branch switching. Therefore, accounting for fluctuations in power demand when reconfiguring the network and positioning capacitors is of paramount importance. Nevertheless, incorporating changes in power demand while simultaneously optimizing branch configurations and addressing reactive power in radial feeders can complicate the computational aspects of the problem, leading to increased processing times. Conversely, disregarding the consumption patterns on the demand side can result in inaccurate calculations of distribution losses and related costs. Consequently, this study delves into the influence of demand patterns on the problem of network topology modification and capacitor assignment considering capacitor and switches investment. It aims to determine whether taking into account load variability is merely an option or an indispensable factor in minimizing the cost of energy losses, switching expenses, and reactive power installation budget via the placement of capacitors and altering the topology of the network. The analysis was carried out on multiple distribution grids using a classical optimization means known as a mathematical programming language (AMPL).